Pendekatan Pendidikan Atau Dakwah Para Wali di Pulau Jawa - Rubini Rubini (STAI Masjid Syuhada Yogyakarta, 2015)
Walisongo is the name of a council or board of missionary propaganda. If there is one parent is away or died then it will soon be replaced by another guardian. Walisongo era is the era of the end of the dominance of the Hindu - Buddhist cultural heritage to be replaced with Islamic culture. They are a symbol of the spread of Islam in Indonesia. Particularly in Java. Of course many other figures who also play a role. But they are very big role in establishing the Islamic kingdom in Java, also its influence on the culture of the community at large as well as direct propaganda, making